SAFETY AND EFFECTIVENESS OF TRI VALENT INACTIVATED SPLIT VIRION INFLUENZA VACCINE IN PATIENTS WITH RHEUMATOID DISORD ERS - D. V. Bukhanova; В. S. Belov; G. M. Tarasova; Sh. F. Erdes; T. V. Dubinina; G. V. Lukina; M. V. Cherkasova; M. E. Diatroptov (Klinicist, 2018)
Objective: to evaluate the safety and effectiveness of vaccination with trivalent split virion influenza vaccine in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS), estimate the effect of vaccination on rheumatoid disorder (RD) activity and influenza and influenzalike illnesses morbidity.Materials and methods. The study included 86 patients (58 females and 28 males aged 22–82 years) with RDs (52 patients with RA and 34 patients with AS), as well as 40 subjects without RD (control group). At the time of study inclusion, all patients were receiving drug therapy. Duration of RD varied from 2 months to 46 years. The Vaxigrip vaccine containing the currents trains of the flu virus for 2016–2017 season or 2017–2018 season was administered subcutaneously as 1 dose (0.5 ml) with continuing antirheumatic therapy. The main control stages were visits 1, 3, and 6 months after vaccination. During the visits, standard clinical and labtests, clinical examination with disease activity evaluation were performed.Results. In 98 patients, vaccination tolerability was high, no post vaccination reactions were observed. In 20 cases, pain, swelling, and hyperemia of the skin 2 cm in diameter at the point of vaccination were observed; in 8 cases, low-grade fever, myalgia, discomfort, headache were observed. No RD flares or development of new autoimmune disorders were diagnosed during the follow-up period. No cases of influenza or influenza-like illnesses were registered during the follow-up period.Conclusion. The obtained data demonstrate high tolerability, clinical effectiveness of trivalent split virion influenza vaccine in patients with RA and AS.